Nontypeable Haemophilus influenzae Otitis Media: Mastoiditis and Meningitis Complicated with Central Venous Thrombosis in an Immunocompetent Child - Erdem Gönüllü; Nesrin Özkan; Ahmet Soysal; Engin Acıoğlu; Emine Betül Tavil; Selin Nar Ötgün; Metin Karaböcüoğlu (Case Reports in Infectious Diseases)
Implementation of the Haemophilus influenzae type B (Hib) conjugate vaccine brought about a reduction in the number of cases and morbidity from type B but an increase in nontypeable strain infections. Nontypeable Haemophilus influenzae (NTHi) commonly colonizes children’s upper respiratory tract and causes otitis media, sinusitis, and bronchitis. Invasive NTHi diseases, such as meningitis and septicemia, have rarely been reported. Herein, we discuss a previously healthy, fully immunized 3-year-old girl presented with otitis media and mastoiditis leading to meningitis caused by NTHi complicated with central venous thrombosis. She was treated with antibiotics, mastoidectomy and ventilation tube insertion, and anticoagulation therapy and recovered uneventfully. Through this case, we wish to share our unique clinical experience that NTHi should be born in mind as a potential pathogen that can cause meningitis in previously healthy children, which may be helpful in future cases.